2020
DOI: 10.7150/ijms.40918
|View full text |Cite|
|
Sign up to set email alerts
|

PDLSCs Regulate Angiogenesis of Periodontal Ligaments via VEGF Transferred by Exosomes in Periodontitis

Abstract: Abnormal angiogenesis is one of the significant features in periodontitis leading to progressive inflammation, but angiogenic changes of periodontal ligaments under inflammatory condition were rarely reported. Periodontal ligament stem cells (PDLSCs) were a kind of dental stem cells associated with vascularization. Here we investigated the alteration of angiogenesis of periodontal ligament in periodontitis, and revealed an exosome-mediated pathway to support the effect of PDLSCs on angiogenic improvement. Vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 33 publications
3
62
0
Order By: Relevance
“…Abnormal angiogenesis is a significant feature of periodontal inflammation 71 . Mesenchymal stem cells (MSCs), including PDLSCs, have been shown to promote angiogenesis, in which autophagy plays a role 72‐74 . The secretion of angiogenin (Ang) and basic fibroblast growth factor (bFGF), two important angiogenesis‐promoting cytokines, was upregulated under inflammatory conditions 68 .…”
Section: Autophagy and Periodontal Inflammationmentioning
confidence: 99%
“…Abnormal angiogenesis is a significant feature of periodontal inflammation 71 . Mesenchymal stem cells (MSCs), including PDLSCs, have been shown to promote angiogenesis, in which autophagy plays a role 72‐74 . The secretion of angiogenin (Ang) and basic fibroblast growth factor (bFGF), two important angiogenesis‐promoting cytokines, was upregulated under inflammatory conditions 68 .…”
Section: Autophagy and Periodontal Inflammationmentioning
confidence: 99%
“…DPSCs, PDLSCs, SHED, SCAP human ultracentrifugation [112,114,[116][117][118]124,125,128,[132][133][134]141] SMCs (maxilla), PCs rat ultracentrifugation [138] DPSCs human Oral mucosa MSCs human density gradient differential centrifugation [142] DPSCs: dental pulp stem cells; PDLSCs: periodontal ligament stem cells; SHEDs: stem cells from exfoliated deciduous teeth; GMSC: gingival mesenchymal stem cells; SMC: sinus mucosa-derived cells; PCs: mandibular periosteum-derived cells; SCAP: stem cells from apical papilla; N.A. : not available.…”
Section: Cell Type Cell Source Isolation Methods Referencesmentioning
confidence: 99%
“…According to Zhang et al, inflammation was responsible for miR-17-5p down-regulation in PDLSCs which, in turn, accounted for increased expression of VEGFA in exosomes derived from inflamed PDLSCs. The exosomes-mediated transfer of VEGFA to endothelial cells finally contributed to the increased vascularization of periodontal ligaments in periodontitis ( Figure 4D) [128].…”
Section: Current and Emerging Treatment Optionsmentioning
confidence: 97%
“…Angiogenesis, which provides nutrition and oxygen to the surrounding cells, is a vital step in bone healing. Exosomes derived from multiple types of cells, including the bone marrow-derived MSCs (BMSCs) 66 , 67 , ADSCs 68 - 70 , human placenta-derived MSCs (hP-MSCs) 71 , 72 , periodontal ligament stem cells (PDLSCs) 73 promote in vitro proliferation, migration, and tube formation of endothelial cells.…”
Section: Exosome-based Therapeutics For Craniofacial and Dental Applimentioning
confidence: 99%
“…In vitro studies have shown that exosomes involved in inflammatory signal transfer and periodontitis progression, which may provide therapeutic targets for periodontal regeneration 76 , 90 , 91 . Royo et al demonstrated that exosomes derived from PDLSCs regulate angiogenesis via the exosome-mediated transfer of miR-17-5p-targeted VEGFA 73 . Additionally, SHEDs-derived exosomes enhance PDLSCs osteogenic differentiation partly due to the presence of Wnt3a and BMP2 in the exosomes.…”
Section: Exosome-based Therapeutics For Craniofacial and Dental Applimentioning
confidence: 99%